Bacterial polyphosphates induce CXCL4 and synergize with complement anaphylatoxin C5a in lung injury - Roewe, Julian; Walachowski, Sarah; Sharma, Arjun; Berthiaume, Kayleigh A.; Reinhardt, Christoph; Bosmann, Markus (Frontiers in Immunology, 2022)
Polyphosphates are linear polymers of inorganic phosphates that exist in all living cells and serve pleiotropic functions. Bacteria produce long-chain polyphosphates, which can interfere with host defense to infection. In contrast, short-chain polyphosphates are released from platelet dense granules and bind to the chemokine CXCL4. Here, we report that long-chain polyphosphates induced the release of CXCL4 from mouse bone marrow-derived macrophages and peritoneal macrophages in a dose-/time-dependent fashion resulting from an induction of CXCL4 mRNA. This polyphosphate effect was lost after pre-incubation with recombinant exopolyphosphatase (PPX) Fc fusion protein, demonstrating the potency of long chains over monophosphates and ambient cations. In detail, polyphosphate chains >70 inorganic phosphate residues were required to reliably induce CXCL4. Polyphosphates acted independently of the purinergic P2Y1 receptor and the MyD88/TRIF adaptors of Toll-like receptors. On the other hand, polyphosphates augmented LPS/MyD88-induced CXCL4 release, which was explained by intracellular signaling convergence on PI3K/Akt. Polyphosphates induced Akt phosphorylation at threonine-308. Pharmacologic blockade of PI3K (wortmannin, LY294002) antagonized polyphosphate-induced CXCL4 release from macrophages. Intratracheal polyphosphate administration to C57BL/6J mice caused histologic signs of lung injury, disruption of the endothelial-epithelial barrier, influx of Ly6G+ polymorphonuclear neutrophils, depletion of CD11c+SiglecF+ alveolar macrophages, and release of CXCL4. Long-chain polyphosphates synergized with the complement anaphylatoxin, C5a, which was partly explained by upregulation of C5aR1 on myeloid cells. C5aR1-/- mice were protected from polyphosphate-induced lung injury. C5a generation occurred in the lungs and BALF of polyphosphate-treated C57BL/6J mice. In conclusion, we demonstrate that polyphosphates govern immunomodulation in macrophages and promote acute lung injury.